2021
DOI: 10.1007/s11904-021-00585-8
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Digital Assessments in Screening for HIV-Related Cognitive Impairment: a Review

Abstract: Purpose of Review While traditional neuropsychological tests are the gold standard in screening for HIV-related cognitive impairment, computerized neuropsychological assessment devices (CNADs) offer an alternative to these time-and resource-intensive batteries and may prove to be particularly useful for remote assessments or longitudinal monitoring. This review seeks to describe the benefits, limitations, and validity of CNADs in the evaluation of HIV-associated neurocognitive disorder (HAND). Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Two reviews 10 , 68 reported that, by 2013, there had been a total of 36 studies examining 40 different screening tests, subtests, or short batteries of individual neuropsychological tests as screening tools for HAND. Also, a new review 48 found 23 additional studies presenting data on 18 different screening tests for HAND; several screeners were novel, based on a computerized assessment or mobile-based screeners (for a review, see Robbins et al 2021; 48 Wilson 2021 69 ). The strengths and the weaknesses of these screening tests are presented elsewhere.…”
Section: Screening For Cognitive Impairmentmentioning
confidence: 99%
“…Two reviews 10 , 68 reported that, by 2013, there had been a total of 36 studies examining 40 different screening tests, subtests, or short batteries of individual neuropsychological tests as screening tools for HAND. Also, a new review 48 found 23 additional studies presenting data on 18 different screening tests for HAND; several screeners were novel, based on a computerized assessment or mobile-based screeners (for a review, see Robbins et al 2021; 48 Wilson 2021 69 ). The strengths and the weaknesses of these screening tests are presented elsewhere.…”
Section: Screening For Cognitive Impairmentmentioning
confidence: 99%
“…These tools will need rigorous validation in the population in which they are deployed. The “trans diagnostic approach” in which it is recognized that mental health disorders often co‐occur and may have a shared underlying pathology has been helpful for the diagnosis and treatment of mental illness in resource‐limited settings and would need to be adapted to include identification and treatment of age‐related cognitive disorders [ 37 , 38 ]. Follow country‐based innovations where HIV services are evolving and adapting to changing needs …”
Section: Discussionmentioning
confidence: 99%
“…Digital cognitive assessment tools have been developed to replace and improve upon traditional cognitive measures, but their development remains in the early stages ( 30 ). A range of issues need to be solved.…”
Section: Mini Literature Reviewmentioning
confidence: 99%